(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: Intracranial Meningiomas are the most common primary brain tumor in adult which are predominantly non-malignant. Surgical intervention is the goldstandard treatment option for intracranial meningiomas but the surgical outcomes are influenced by various epidemiological risk factors. Understanding these factors is essential for a precise decision-making process, application of effective therapeutic intervention and prognostication. Aims: This study aimed to identify the possible predictive factors influencing surgical outcome in patients with intracranial meningioma. Materials and Methods: This Prospective Observational Study included 34 patients of intracranial Meningioma who had surgery in the Department of Neurosurgery, Chittagong Medical College Hospital between February 2022 to August 2023. Outcome measures were the Glasgow Outcome Scale (GOS) and Karnofsky Performance Status (KPS) score at the immediate postoperative period, “0” postoperative day, at the time of discharge, 1 month, 3 months, and 6 months post-surgery. GOS score 1-3 was considered as poor outcome. Results: The mean age of the patients was 46.8±12.6 years and 70.6% were female. Most of the patients were in either ASA class I (35.3%) or Class II (55.9%), and the median KPS score was 80% before surgery. Twenty-eight (82.4%) patients survived at least six months following surgery and the 6-months mortality rate was 17.6%. Twenty-seven (79.4%) patients had a good outcome and 7 (20.6%) patients had a poor outcome. Preoperative KPS score (p=0.024), tumor location (p=0.019), and tumor volume (p=0.003) were found to have a significant association with outcome in univariate analysis. However, none of these factors retained a significant association in multivariate analysis. Conclusions: In conclusion, specific influencing factors for postoperative poor outcomes revealed in univariate analysis in the present study were low preoperative KPS score, skull base meningioma, and large-size tumor Bang. J Neurosurgery 2024; 13(2): 121-129